Investigating the Impact of Store Atmosphere, Product Quality, and Word of Mouth on Purchase Decisions: A Study at Kiroro Bakery: Mengeksplorasi Dampak Atmosfer Toko, Kualitas Produk, dan Word of Mouth terhadap Keputusan Pembelian: Studi Kuantitatif di Kiroro Bakery - Muhammad Fauzen; Dewi Komala Sari (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to investigate the influence of store atmosphere, product quality, and word of mouth on purchase decisions at Kiroro Bakery in Sidoarjo. A quantitative approach was employed, utilizing a nonprobability sampling method with accidental sampling. The sample comprised 100 respondents who were customers of Kiroro Bakery. Data analysis involved multiple linear regression using SPSS Statistics version 25. The findings revealed significant effects of store atmosphere, product quality, and word of mouth on purchase decisions. These results contribute to a deeper understanding of consumer behavior in the context of bakery purchasing decisions, highlighting the importance of these factors. Highlights: The study examines the impact of store atmosphere, product quality, and word of mouth on purchase decisions at Kiroro Bakery. The research adopts a quantitative approach and utilizes multiple linear regression analysis. The findings reveal significant effects of store atmosphere, product quality, and word of mouth on consumer purchase decisions, emphasizing the importance of these factors in the bakery industry. Keywords: Store atmosphere, product quality, word of mouth, purchase decisions, Kiroro Bakery